2021
DOI: 10.1017/s0030605320001180
|View full text |Cite
|
Sign up to set email alerts
|

Globally important refuge for the loggerhead sea turtle: Maio Island, Cabo Verde

Abstract: One of the largest nesting colonies of the Vulnerable loggerhead sea turtle Caretta caretta is in Cabo Verde. Here we present the first comprehensive study of loggerhead turtle nesting on the island of Maio in Cabo Verde. During 2016–2019 we monitored 38 km of undeveloped sandy beaches that have minimal artificial lighting and where all nesting on Maio takes place. We counted 4,063 nests in 2016, 5,429 in 2017, 14,364 in 2018 and 7,937 in 2019. The estimated total number of females was 1,016, 1,357, 3,591 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Here we describe the degree of nesting beach selection and the consistency of intra-beach site selection for egg deposition over 8 years in one of the largest loggerhead turtle Caretta caretta colonies: Maio Island on Cabo Verde, West Africa (Cozens et al, 2011; Dutra & Koenen, 2014; Patino-Martinez et al, 2022a). In the last decade (2012–2021) the number of nests has increased on Maio Island, with a mean of 19,415 ± SD 16,450 nests per season during 2017–2021 (Patino-Martinez et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe the degree of nesting beach selection and the consistency of intra-beach site selection for egg deposition over 8 years in one of the largest loggerhead turtle Caretta caretta colonies: Maio Island on Cabo Verde, West Africa (Cozens et al, 2011; Dutra & Koenen, 2014; Patino-Martinez et al, 2022a). In the last decade (2012–2021) the number of nests has increased on Maio Island, with a mean of 19,415 ± SD 16,450 nests per season during 2017–2021 (Patino-Martinez et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Maio Island represents a great input for the loggerhead Northeast Atlantic subpopulation (Patino-Martinez et al, 2021) and, given the high mortality rates among in situ clutches reported here, it is recommended that protection measures are implemented. In the past, clutches and turtles were extensively poached by local communities (Cabrera et al, 2000;Lino et al, 2010;Cozens et al, 2011;Marco et al, 2012;Hancock et al, 2017), contributing to population decline.…”
Section: Conservation Implications and Limitationsmentioning
confidence: 98%
“…The North East Atlantic subpopulation of loggerhead sea turtles (C. caretta), is listed as Endangered by the IUCN Red List of Threatened Species (Casale and Marco, 2015). Recent findings suggest a higher number of loggerhead turtles nesting in Cabo Verde than previously estimated, and that this might be the largest nesting subpopulation of this species globally (Patino-Martinez et al, 2021). However, the vast majority of the nests are concentrated in the Cabo Verde archipelago, making this subpopulation particularly vulnerable to habitat loss and degradation (Casale and Marco, 2015).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Neophytes are usually smaller than remigrants in marine turtles (Lamont et al 2014, Stokes et al 2015; hence, increasing numbers of small nesting females might suggest improved recruitment to the adult population (Arendt et al 2013, Omeyer et al 2021. Nest counts have increased recently across the archipelago, and during the 2018 nesting season, the number of nesting loggerhead turtles at Cabo Verde tripled in comparison to the previous year (2017), which was a record year for the NN registered (Marco et al 2012a, 2018b, Laloë et al 2020, Patino-Martinez et al 2022). This could be interpreted as evidence of an increased population size, but caution is needed because increased NN might also result from changes in the RI and the total number clutches laid per season, even if population size remains unmodified (Hays et al 2022).…”
Section: Long-term Reproductive Output and Conservation Implicationsmentioning
confidence: 99%